The Frenzy Post-Appointment of Anies Rasyid Baswedan As A Presidential Candidate - Abdul Rahman,; Emanuel Omedetho Jermias,; Nurlela, (Technium Social Sciences Journal, 2023)
Judging from the electoral political indicators, Indonesia's democratic achievements are impressive. There is not the slightest doubt about the achievements of electoral democracy in Indonesia. The world recognizes Indonesia as the largest democratic country after the United States and India. One indicator of democracy is the presence of political parties as a means for the public to convey their aspirations during general elections. Indonesia will hold general elections in 2024. This study aims to elaborate on Indonesia's political dynamics after the determination of Anies Rasyid Baswedan as a presidential candidate. The methods used in this study are topic determination, heuristics, criticism, interpretation, and historiography. The results of the research show that various political dynamics that occur in the face of the 2024 election, one of which is the appointment of Anies Rasyid Baswedan as a presidential candidate. Debate at the elite level as well as in the general public regarding the formation of a coalition for change fronted by the National Democratic Party, the Prosperous Justice Party and the Democratic Party.